Reading epilepsy. Issue 5 (21st September 2010) - Miller, Sarah; Razvi, Saif; Russell, Aline
Abstract : Reading epilepsy is a rare epilepsy syndrome triggered by language related activity, in particular reading. Here we describe a patient with reflex seizures brought on specifically by reading in Arabic. The types of reading epilepsy, their typical clinical features, probable pathophysiology and management are discussed.